Exploring potentials of introducing sustainability in procurement of rolling stock for Bangladesh Railway - Jerry, Jebunnesa (BRAC University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.